KEPEMIMPINAN KEPALA SEKOLAH YANG MENDISIPLINKAN KERJA GURU (STUDI KASUS DI SMK NEGERI LABUANG KABUPATEN POLEWALI MANDAR) - Yunus, Rudi (Pascasarjana Universitas Negeri Makassar, 2016)
The study aims at examining the forms of discipline on teachers’ work, factors which influence it, and the functions of leadership of the principal to discipline teachers work.The study is a qualitative research with a case study. The study was conducted at SMKN Labuang in Polewali Mandar distirct. The Informants of the study were the principal, vice principal and teacher. Data were collected through interview, observation, and documentation. Data were analyzed by employing qualitative analysis using interactive model or Miles and Huberman’s model.The results of the study revealed that (i) the forms of discipline on teacher’s work at SMKN Labuang in Polewali Mandardistrict were preventive disciplie in forms of suggestion and afirmatife message, and correctivediscipline in forms of verbal reprimand, written reprimand, and incentive cuts; howefer, the form of discipline implemented by the principal of SMKN Labuang in Polewali Mandar district was preventive discipline, (ii) factors which caused teachers of SMKN Labuang in Polewali Mandar district lack of discipline were the internal and external factors. The internal factors were lack of competence of teacher’s personal, lack of good time management, and ignorance of time; whereas, the external factors were transportation,family, office demand, and leadership style of the principal, and (iii) the functions of leadership of the principal of SMKN Labuang to discipline teachers’ work were implementing the functions of instructive, delegative, consultative, participative leadership, and controlling function; however, the leadership function which generally implemented was instructive function.Manusia merupakan makhluk sosial yang diciptakan untuk berinteraksi